Constructing Knowledge Database in Decision Making - Dihovicni, Djordje N. (Communications - Scientific letters of the University of Zilina, 2011)
The paper describes solving problem of constructing knowledge database of a decision making in process safety. It provides analyses of the requirements as well the analyses of the system incidents caused by specification, design and the implementation of the project. Main focus of this scientific paper is highlighted on practical stability problem and conditions for optimal performance of safe fault-tolerant controllers, I/O, engineering and pressure transmitters. Algorithm of decision making in process safety is developed and the system has been realized taking into account C# approach in Windows environment.